Breeding systems in tropical areas: weaning precocious - Gonzaga Silveira, Luiz Guilherme [UNESP]; Miyashita Piona, Mauricio Nobuyuki [UNESP]; Mousquer, Claudio Jonasson [UNESP]; Gomes, Rafael Silveira [UNESP]; Silveira, Antonio Carlos (Univ Federal Ceara, Centro Ciencias Agrarias, 2016)
This work brings to quantify and provide benefits to using this early weaning protocol, showing the benefits for the calf and for females, it is multiparous and / or mostly gilts. Several studies on weaning weight in cattle, which show great variation in the average of this feature. This variation may be the result of genetic variation between arrays, food, reproductive and health management that varies from region to region and from farm to farm, in addition to the different programs of selection and genetic improvement of beef cattle used in the country.
Keywords: Young; reproduction; animal nutrition; feed management; animal science